Effects of PCBs 52 and 77 on Th1/Th2 balance in mouse thymocyte cell cultures - Sandal, S; Yilmaz, B; Godekmerdan, A; Kelestimur, H; Carpenter, DO (Taylor & Francis Ltd, 2005)
Polychlorinated biphenyls (PCBs) are industrial chemicals that have been released into the environment, resulting in widespread and persistent contamination. PCBs exist as 209 different congeners depending on the chlorine substitution on the biphenyl rings, and the physical properties and toxic effects of different PCB congeners are structure-dependent. We have tested an ortho-substituted, noncoplanar congener, 2,2 ',5,5 '-tetrachlorobiphenyl (PCB 52), and a non-ortho-substituted coplanar congener, 3,3 ',4,4 '-tetrachlorobiphenyl (PCB 77), for their effects on the T helper 1 (Th1) and T helper 2 (Th2) lymphocyte balance. The experiments were performed in 10 mu g/ml concanavalin A (Con A)-stimulated and nonstimulated thymocytes for determination of cytokine production profiles. Interferon-gamma (produced by Th1 cells) and interleukin (IL)-10 (produced by Th2 cells) concentrations were measured in the supernatants at 12 and 24 hr after treatment with PCBs. PCBs 52 and 77 caused significant increases in interferon-gamma levels at 12 and 24 hr in both Con A-stimulated and nonstimulated media. IL-10 levels were significantly reduced at two interval periods by PCBs 52 and 77 in cultures with and without Con A. Our results show that the cytokine production profile was significantly shifted to Th1 by both ortho-substituted and coplanar PCB congeners in mouse thymocyte cultures.
Keywords: Ah receptor; cytokines; tissue culture; interferon-gamma; interleukin I